2016
DOI: 10.1155/2016/2020146
|View full text |Cite
|
Sign up to set email alerts
|

Key Features in the Management of Pulmonary Carcinosarcoma

Abstract: Pulmonary carcinosarcoma represents a category of extremely rare tumours accounting for 0.1% of all lung malignancies. It is defined as a poorly differentiated non-small-cell carcinoma that contains a component of sarcoma or sarcoma-like elements. These biphasic tumours typically have a poor prognosis due to late diagnosis and early metastases. Preoperative tissue diagnosis is usually difficult due to the heterogeneity of the tumour, with biopsies often just reflecting one element of the tumour. By means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Primary lung carcinosarcoma is a rare tumour, representing roughly 0.1–1.0% of all lung cancers [ 7 9 ]. These tumours show a roughly 7 : 1 male-to-female ratio, present at a median age of 65 years, and are frequently associated with a history of heavy smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Primary lung carcinosarcoma is a rare tumour, representing roughly 0.1–1.0% of all lung cancers [ 7 9 ]. These tumours show a roughly 7 : 1 male-to-female ratio, present at a median age of 65 years, and are frequently associated with a history of heavy smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors proposed new therapeutic strategies based on better knowledge of the carcinogenesis of sarcomatoid carcinomas. Radiotherapy is also a well-established choice of treatment, which can reduce the local recurrence rate in cases with residual tumor [10]. Our patient is free of disease during this six-month follow-up without any adjuvant treatment.…”
Section: Discussionmentioning
confidence: 67%
“…It features easy relapse after surgical resection and resistance to radiotherapy and chemotherapy 46. The Mayo Clinic conducted a study and showed that the 5-year preoperative and postoperative survival for pulmonary CS patients was 21.3% and 28.7%, respectively, with an average postoperative survival of 9 months 47. The genomic alterations of pulmonary CS have been identified by using next-generation sequencing analysis 48.…”
Section: Discussionmentioning
confidence: 99%